2019
DOI: 10.3389/fmicb.2018.03243
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive; or Does It Really Matter? Level of Congruency Between Trophic Modes in Total and Active Fungal Communities in High Arctic Soil

Abstract: Describing dynamics of belowground organisms, such as fungi, can be challenging. Results of studies based on environmental DNA (eDNA) may be biased as the template does not discriminate between metabolically active cells and dead biomass. We analyzed ribosomal DNA (rDNA) and ribosomal RNA (rRNA) coextracted from 48 soil samples collected from a manipulated snow depth experiment in two distinct vegetation types in Svalbard, in the High Arctic. Our main goal was to compare if the rDNA and rRNA metabarcoding temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 78 publications
4
20
0
Order By: Relevance
“…This approach can even be used for targeting the universal DNA barcode region for fungi, the nuclear ribosomal internal transcribed spacer region (ITS) [15], and the few available studies showed that rRNA derived fungal communities differ from those derived from rDNA at the levels of richness, abundance of certain taxa and overall community composition [14,16,17,18,19]. However, such studies comparing total and active fungal communities have mostly been carried out either in surface soils from different biomes [14,16,17,20], or in communities associated with different plant species [19,21], but equivalent studies in subsurface aquatic ecosystems are largely missing.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can even be used for targeting the universal DNA barcode region for fungi, the nuclear ribosomal internal transcribed spacer region (ITS) [15], and the few available studies showed that rRNA derived fungal communities differ from those derived from rDNA at the levels of richness, abundance of certain taxa and overall community composition [14,16,17,18,19]. However, such studies comparing total and active fungal communities have mostly been carried out either in surface soils from different biomes [14,16,17,20], or in communities associated with different plant species [19,21], but equivalent studies in subsurface aquatic ecosystems are largely missing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to soil samples we observed a similar trend in decaying wood samples. Concerning Agaricomycetes there is a notable difference in RNA:DNA ratio, that is higher in wood, dominated by saprotrophs [89][90][91], than in soils where mycorrhizal symbionts thrive [31,89,[92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of microbial, either prokaryotic or eukaryotic, community metabarcoding on both eDNA and eRNA highlighted either a strong correlation between "active" (RNA-based) and "total" (DNA-based) microbial communities [25][26][27][28][29], or on the contrary identified significant differences between the different datasets [28,30,31]. For example, a greater taxonomic alpha diversity was often, but not always (see [31]), deduced from DNA compared to RNA datasets [30][31][32][33]. This could be a consequence of the presence of DNA from dead or resting organisms (legacy DNA) that do not, or no longer, participate to ecosystem processes [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations